Design Sensitivity Analysis of a Plate-Finned Air-Cooled Condenser for Low-Temperature Organic Rankine Cycles. Issue 11 (13th August 2017) - Kaya, Alihan; Lazova, Marija; Bağcı, Özer; Lecompte, Steven; Ameel, Bernd; De Paepe, Michel
ABSTRACT: Due to increasing world energy demand and environmental concerns, sustainable energy production has become crucial. Among sustainable energy sources such as solar, wind, and geothermal, industrial waste heat (heat normally released to the environment) has a big potential. Organic Rankine cycles (ORCs) are promising systems for utilizing low-temperature (100–250°C) waste heat. For an ORC system, the condenser is a key component. An accurate condenser design is important for cycle efficiency and system cost. In the literature, there are in-tube condensation correlations that are used to design condensers. However, they are not necessarily valid for low-temperature ORC conditions and working fluids, and that might lead to inaccurate end designs. This study comprises a summarized literature survey about in-tube condensation correlations. Then an iterative heat exchanger design methodology is proposed that allows performing a design sensitivity analysis on a V-shaped condenser within an input range of geometric parameters and boundary conditions. Nineteen correlations are implemented to calculate rating parameters like pressure drops, total transferred heat, overall heat transfer coefficient, size, cost and degree of subcooling. The deviations at these parameters are represented as the coefficient of variation that indicates the design condition regions where the prediction methods differ or not.